The stellar kinematics of corotating spiral arms in Gaia mock observations - Hunt, Jason A. S.; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We have observed an N-body/smoothed particle hydrodynamics simulation of a Milky Way-like barred spiral galaxy. We present a simple method that sampl